Emotion dysregulation in ADHD and other neurodevelopmental conditions: a co-twin control study - Rebecka Astenvald; Matilda A. Frick; Janina Neufeld; Sven Bölte; Johan Isaksson (BMC, 2022)
Abstract Background Emotion dysregulation (ED) is common in attention-deficit/hyperactivity disorder (ADHD) and often results in adverse outcomes. However, ED has been suggested as a transdiagnostic construct, why the specific association between ADHD and ED when adjusting for other mental health conditions needs further investigation. It is also important to determine the aetiological basis of the association between ADHD and ED to inform the theoretical conceptualization of ADHD. Method This study used a co-twin control design, including a sample of dizygotic (DZ) and monozygotic (MZ) twins (N = 389; 45.8% females, age = 8-31 years, MZ twin pairs 57.6%). ED was assessed using the dysregulation profile from the parent-rated Child Behaviour Checklist and its adult version. Regression analyses were used across individuals and within the pairs, while adjusting for diagnoses of autism, intellectual disability, other neurodevelopmental conditions and affective conditions. Results ADHD was significantly associated with ED, even when adjusting for age, sex, attention problems and other mental health conditions, and was the diagnosis most strongly associated with ED. Within-pair analyses revealed that twins with ADHD had higher levels of ED compared to their co-twin without ADHD. This association remained within DZ twins and was non-significant in the MZ subsample, with non-overlapping confidence intervals between the DZ and MZ estimates. Conclusion ADHD is strongly and in part independently linked to ED, stressing the importance of early detection and treatment of emotional difficulties within this group. The findings from the within-pair analyses indicate a genetic influence on the association between ADHD and ED.